Identification, characterization, and rescue of CRISPR/Cas9 generated wheat SPO11‐1 mutants. Issue 2 (10th December 2022) - Hyde, Lucy; Osman, Kim; Winfield, Mark; Sanchez‐Moran, Eugenio; Higgins, James D.; Henderson, Ian R.; Sparks, Caroline; Franklin, F. Chris H.; Edwards, Keith J.
Summary: Increasing crop yields through plant breeding is time consuming and laborious, with the generation of novel combinations of alleles being limited by chromosomal linkage blocks and linkage‐drag. Meiotic recombination is essential to create novel genetic variation via the reshuffling of parental alleles. The exchange of genetic information between homologous chromosomes occurs at crossover (CO) sites but CO frequency is often low and unevenly distributed. This bias creates the problem of linkage‐drag in recombination 'cold' regions, where undesirable variation remains linked to useful traits. In plants, programmed meiosis‐specific DNA double‐strand breaks, catalysed by the SPO11 complex, initiate the recombination pathway, although only ~5% result in the formation of COs. To study the role of SPO11‐1 in wheat meiosis, and as a prelude to manipulation, we used CRISPR/Cas9 to generate edits in all three SPO11‐1 homoeologues of hexaploid wheat. Characterization of progeny lines shows plants deficient in all six SPO11‐1 copies fail to undergo chromosome synapsis, lack COs and are sterile. In contrast, lines carrying a single copy of any one of the three wild‐type homoeologues are phenotypically indistinguishable from unedited plants both in terms of vegetative growth and fertility. However, cytogenetic analysis of the edited plants suggests that homoeologues differ in their ability to generate COs and in the dynamics of synapsis. In addition, we show that the transformation of wheat mutants carrying six edited copies of SPO11‐1 with the TaSPO11‐1B gene, restores synapsis, CO formation, and fertility and hence opens a route to modifying recombination in this agronomically important crop.